AB0139 Active vitamin D hormone antagonizes age-induced functional alterations in human osteoblasts. (23rd January 2014) - Oelzner, P.; Franke, S.; Hofmann, G.; Wolf, G.
Abstract : Background: Increased production and accumulation of advanced glycation endproducts (AGEs) in chronic inflammatory diseases such as rheumatoid arthritis (RA) and during physiological aging may contribute to osteoporosis by suppression of bone formation. On the other hand, RA and older age are frequently associated with vitamin D deficiency. In contrast to the suppressive effects of AGEs on osteoblast (OB) proliferation, the active vitamin D metabolite 1.25-dihydroxyvitamin D3 (1, 25D3) stimulates OB proliferation and bone formation. Objectives: The aim of our study was to investigate if 1, 25D3 is able to prevent AGE-induced functional alterations of OB. Methods: Human OB were isolated and cultured from bone tissue of 10 patients with knee osteoarthritis and joint replacement. Cells from passages 3 - 7 were treated for 48 hours with control bovine serum albumin (Co-BSA), AGE-BSA and AGE-BSA+1, 25D3, respectively (medium concentrations: 5 mg/ml AGE-BSA and Co-BSA, respectively; 100 pmol/l and 500 pmol/l 1, 25D3). MRNA and protein expression of bone alkaline phosphatase (bALP), collagen type 1 (Col1) and osteocalcin (OC) were investigated by qRT-PCR and Western Blot-analysis, respectively. For measurement of proliferation and vitality BrdU- and MTT assays were used, respectively. Results: In comparison with control-BSA (mRNA expression 100%) the treatment with AGE-BSA led to a significant reduction of relative mRNA expression of bALP (77±5%; p<0.05), Col 1 (58±35%; p<0.05) und OC (67±24%; p<0.05). The co-treatment with 1, 25D3 resulted in a complete inhibition of the AGE-BSA induced suppression of mRNA-expression. The relative mRNA expression after co-treatment with 100 pmol/l and 500 pmol/l 1, 25D3 was significantly higher (p<0.05) in comparison with the AGE-BSA-treated OB (115±11% and 126±15% for bALP, 100±15% and 152±51% for Col1 and 4243±269% and 6121±2789% for OC, respectively). Furthermore, the relative mRNA expression of OC was significantly higher in comparison to control-BSA-treated OB after co-treatment with both 1, 25D3 concentrations. Corresponding results were observed for protein expression. Conclusions: The results of the investigations indicate the ability of active vitamin D hormone to antagonize completely suppressive effects of AGEs on selective functions of OB in vitro. 25-hydroxyvitamin D3 can be metabolized into active vitamin D hormone in OB. Therefore, in diseases with both AGE accumulation and a high frequency of vitamin D deficiency such as RA both factors may contribute to potentiation of suppressive effects on bone formation and bone repair. With respect to bone formation, a sufficient vitamin D substitution may be of particular importance in RA and in older age. Disclosure of Interest: None Declared